Bishop Patrick Byrne and the Korean Catholic Church in Cold War Korea - Han, Jieun (Korea journal, 2020)
After its liberation, Korea was divided in half-the South controlled by the American military government and the North by the Soviet Red Army. As rivalry between the United States and the Soviet Union intensified on the Korean Peninsula, in October 1947, Pope Pius XII made a groundbreaking decision to send Bishop Patrick James Byrne to Seoul as the first apostolic visitor to Korea. His appointment was regarded as the Vatican's recognition of Korea as an independent nation, even before the formal establishment of the Republic of Korea on August 15, 1948. Thus, the Cold War in Korea came to take on a significant religious dimension. The Cold War in Korea is generally regarded as a proxy war between the United States and the Soviet Union. However, the Holy See had its own agenda for confronting what it viewed as atheistic communists. In this context, this paper sheds light on Pope Pius XII's papal diplomacy by exploring Bishop Byrne's mission and the relations between the Korean Catholic Church led by Bishop Ro Kinam, the American military government, and the Vatican, in building an independent state in Korea. This paper also examines how anti-communism served as a driving force in the fight against atheistic Marxists and how religious leaders perceived the Cold War in the process of establishing a new state on the Korean Peninsula.